Factors Affecting Fear, Obsession, and Anxiety Associated with COVID-19: A Cross-Sectional Study in Patients Admitted to University Hospital Outpatient Clinics - Savkin, Raziye; Öztop, Mücahit; Bayrak, Gökhan; Büker, Nihal (Erciyes Univ Sch Medicine, 2021)
Objective: During the coronavirus disease 2019 (COVID-19) pandemic, there has been a significant decrease in outpatient visits and hospital admissions. The increased risk of transmission, especially in environments with high contamination such as hospitals, may increase fear, obsession, and anxiety in patients. This study aims to investigate the factors affecting fear, obsession, and anxiety associated with COVID-19 in patients who are admitted to university hospital outpatient clinics. Materials and Methods: This study was conducted from January 2021 to February 2021 at Pamukkale University Hospitals outpatient clinics. Demographic information (age, education, sex, marital status, house sharing, employment, and work schedule) and questions related to COVID-19 (visiting a doctor regularly before the pandemic, positive test results, isolation due to contact, losing a friend/family member because of the disease, and delay/avoidance of medical care because of COVID-19-related concerns) were questioned. Fear of COVID-19 Scale, Obsession with COVID-19 Scale, Coronavirus Anxiety Scale, and Short Form-12 were filled. Results: A total of 535 patients (291 females and 244 males; mean age, 45.59 +/- 16.08 years) participated. The Fear of COVID-19 Scale score was 16.74 +/- 6.60, that of Obsession with COVID-19 Scale was 2.22 +/- 2.74, and that of Coronavirus Anxiety Scale was 0.77 +/- 2.32. Female sex, working from home or flexibly, admission to internal medical sciences, and losing a loved one due to the disease increased COVID-19 fear, obsession, and anxiety (p<0.001). Fear, obsession, and anxiety associated with COVID-19 have negatively affected SF-12 physical and mental scores (p<0.001). Conclusion: The present study suggested that to ensure that treatments can be continued uninterruptedly in patient groups who are at risk in terms of increasing COVID-19 fear, obsession, and anxiety, remote health consultations can be performed.
Keywords: Anxiety; COVID-19; fear; obsession; outpatient clinics; patient admission; Health